EFEITOS DA CARÊNCIA DE CÃLCIO, BORO E ZINCO SOBRE A PRODUTIVIDADE DE SOJA (Glycine Max (L.) MERRILL CV. SANTA ROSA - Rodrigues, Selma Dzimidas; Moraes, José Antonio Proença Vieira de; Rodrigues, João Domingos; Ono, Elizabeth Orika; Delachiave, Maria Elena Aparecida; Pedras, José Figueiredo (REVISTA DE AGRICULTURA, 2015)
EFEITOS DA CARÊNCIA DE CÃLCIO, BORO E ZINCO SOBRE A PRODUTIVIDADE DE SOJA (Glycine Max (L.) MERRILL CV. SANTA ROSA